Analisis Pengaruh Produk Domestik Regional Bruto, Indeks Pembangunan Manusia, Pengangguran, dan Inflasi Terhadap Kemiskinan - Muhammad Syukron Ma'mun; Faiq Fuadi (JURNAL DINAMIKA EKONOMI PEMBANGUNAN, 2023)
This study aims to analyze the effect of gross regional domestic product, human development index, unemployment, and inflation on poverty using panel data for 5 cities in the Ex-Residency of Pati during the 2010-2018 period. In 2018, the poverty rate in the ex-Residency of Pati reached 12% compared to other areas in Central Java. The type of data is secondary data obtained from Central Java Province Statistics Agency. Descriptive analysis and panel data regression analysis methods were used to answer research objectives. The results confirm that gross regional domestic product, human development index, and inflation have a negative effect on poverty. On the contrary, unemployment has a positive effect on poverty.